Iowa Birdline update, December 20, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for December 20, 1993. Highlights include the first reports from the Christmas bird counts. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed